Systemic modulation of peripheral eosinophilia (air pouch model) in Schistosoma mansoni infection - RG Pacheco; HL Lenzi (Memorias do Instituto Oswaldo Cruz, 1997)
Schistosoma mansoni infection induces in their hosts a marked and sustained eosinophilia, which is influenced or modulated by complex mechanisms, that vary according to the phase of infection. To address this phenomenon, we used the air pouch (AP) model in control and infected Swiss webster mice, analyzing the cellular, tissue response and local expression of adhesion molecules [CD18 (beta 2-chain), CD44, ICAM-1 (CD54), L-selectin (CD62L), CD49d (alpha 4-chain), LFA1 (CD11a)]. Infected animals were studied at 3 (pre-oviposition phase), 7 (acute phase), and 14 (chronic phase) weeks after infection (5-6 mice/period of infection). Normal mice were age-matched. Results showed that after egg stimulation, compared with matched controls, the infected mice, at each point of infection, showed a lower eosinophil response in the acute (7 weeks) and chronic phase (14 weeks) of infection. However, when the infected mice were in pre-oviposition phase (3 weeks) their eosinophil response surpassed the control ones. In the AP wall of infected mice, a significant decrease in the expression of ICAM-1 and CD44 in fibroblastic-like cells and a reduction in the number of CD18 and CD11a in migratory cells were observed. The other adhesion molecules were negative or weakly expressed. The results indicated that in the air pouch model, in S. mansoni-infected mice: (1) eosinophil response is strikingly down-regulated, during the acute ovular phase; (2) in the pre-oviposition phase, in contrast, it occurs an up-regulatory modulation of eosinophil response, in which the mechanisms are completely unknown; (3) in the chronic phase of the infection, the down modulation of eosinophil response is less pronounced; 4) Down-regulation of adhesion molecules, specially of ICAM-1 appear to be associated with the lower eosinophil response.